Internal Migration in Developing Countries - Valeria Groppo (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
For people in rural areas of developing countries, finding a better paying job or better education is often only possible by moving - migrating - somewhere else. Moreover, agricultural production, generally the main economic activity in rural areas of developing countries, is risky, affected by droughts and floods. Due to poverty and the limited availability of crop insurance, rural households often rely on distant family members to provide money for buying food, starting a business or maintaining an existing business. The vast majority of moves happen within countries. Focusing on developing regions, this Roundup addresses the following questions: What are the broad trends in internal migration? Do internal migrants and their families really benefit from within-country mobility? What role does internal migration play in the recent urbanization process? The Roundup also documents how policy can increase the development impact of internal migration.
Keywords: 330